Transbronchial Cryobiopsy for the Diagnosis of Interstitial Lung Diseases: CHEST Guideline and Expert Panel Report - Maldonado, Fabien; Danoff, Sonye K; Wells, Athol U; Colby, Thomas V; Ryu, Jay H; Liberman, Moishe; Wahidi, Momen M; Frazer, Lindsy; Hetzel, Juergen; Rickman, Otis B; Herth, Felix J F; Poletti, Venerino; et al. (Chest, 2020)
Transbronchial cryobiopsy (TBC) is increasingly recognized as a potential alternative to surgical lung biopsy (SLB) for the diagnosis of interstitial lung disease (ILD). The goal of this analysis was to examine the literature on TBC as it relates to diagnostic utility and safety to provide evidence-based and expert guidance to clinicians. Approved panelists developed key questions regarding the diagnostic utility and safety of TBC for the evaluation of ILD using the PICO (Population, Intervention, Comparator, Outcome) format. MEDLINE (via PubMed) and the Cochrane Library were systematically searched for relevant literature, which was supplemented by manual searches. References were screened for inclusion, and vetted evaluation tools were used to assess the quality of included studies, to extract data, and to grade the level of evidence supporting each recommendation or statement. Graded recommendations and ungraded consensus-based statements were drafted and voted on using a modified Delphi technique to achieve consensus. The systematic review and critical analysis of the literature based on four PICO questions resulted in six statements: two evidence-based graded recommendations and four ungraded consensus-based statements. Evidence of the utility and safety of TBC for the diagnosis of ILD is limited but suggests TBC is safer than SLB, and its contribution to the diagnosis obtained via multidisciplinary discussion is comparable to that of SLB, although the histological diagnostic yield appears higher with SLB (approximately 80% for TBC vs 95% for SLB). Additional research is needed to enhance knowledge regarding utility and safety of TBC, its role in the diagnostic algorithm of ILD, and the impact of technical aspects of the procedure on diagnostic yield and safety.